Adsorption–desorption and bioavailability of selected micronutrients in tropical peat soil in Sarawak, Malaysia - Abdullah, Mohd. Zulhilmy (2019)
Tropical peatland has a distinctive bio-sequence of concentric forest zones with different forest types. Mature peat swamps in Sarawak comprised of mixed peat swamp forest (MPS), Alan Batu forest (A.Bt), and Alan Bunga forest (A.Bg). These forest types may differ in their decomposition of soil organic matter (SOM) contents, thus affect the availability of micronutrients, since peat soils are generally oligotrophic. This study investigated the availability of copper (Cu), zinc (Zn) and boron (B) to the plants under different forest types. The adsorption and desorption batch experiment were performed using soil samples collected from MPS, A.Bt and A. Bg forests. Further relationship between adsorption and desorption with Cu, Zn and B availability in highly decomposed peat soil type (MPS) were examined in a polybag experiment using Napier grass (Pennisetum purpureum) as the test crop. The adsorption data of Cu were fitted better on the Langmuir’s model while Zn adsorption data were comparable between the model used and B adsorption data was fitted better in the Freundlich’s model. Generally, the Kf and b values were observed in order of Cu > Zn > B. This shows that Cu has a high affinity towards the peat soils surface compare to Zn and B. The MPS forest soils were observed to have slightly high adsorption capacity for Cu, Zn and B. This could emphasize that more decomposed peat materials would influence the affinity of Cu, Zn and B towards peat soil surface. Release of Cu, Zn and B was evaluated with different extractants to determine the available, exchangeable and complex form of micronutrients. The complex form of Cu and Zn is significantly different for MPS soil compare to exchangeable and available form. Copper and Zn were observed to highly bind to the surface of peat soils and the stronger chelating agent needed to desorb them into the soil solution. Release of B has shown no significant differences among extractants used, since B has low affinity towards the soil surface and easily leach out from the soil system. The application of Cu, Zn and B solution with different concentration (0, 1, 3, 5, 10, 20, 30 mg L-1) to the Napier grass planted in peat soils showed that mean dry matter yield has no significant difference among the treatment. The polynomial plot showed the optimum uptake of Cu and Zn (in range of 10 – 20 mg L-1) and B (up to 5 mg L-1). The mean uptake of Zn (0.52 mg plant-1) was higher than Cu (0.11 mg plant-1) and B (0.064 mg plant-1) because Cu has a high affinity towards the soil surface, while B easily leaches out to the soil solution system. Therefore, considering 4R (right source, right rate, right time and right place) nutrient stewardship is important to the improved nutrient use efficiency of the plant.